Technical Note: GATE‐RTion: a GATE/Geant4 release for clinical applications in scanned ion beam therapy. Issue 8 (13th June 2020) - Grevillot, L.; Boersma, D. J.; Fuchs, H; Aitkenhead, A.; Elia, A.; Bolsa, M.; Winterhalter, C.; Vidal, M.; Jan, S.; Pietrzyk, U.; Maigne, L.; Sarrut, D.
Abstract : Purpose: GATE‐RTion is a validated version of GATE for clinical use in the field of light ion beam therapy. This paper describes the GATE‐RTion project and illustrates its potential through clinical applications developed in three European centers delivering scanned proton and carbon ion treatments. Methods: GATE‐RTion is a collaborative framework provided by the OpenGATE collaboration. It contains a validated GATE release based on a specific Geant4 version, a set of tools to integrate GATE into a clinical environment and a network for clinical users. Results: Three applications are presented: Proton radiography at the Centre Antoine Lacassagne (Nice, France); Independent dose calculation for proton therapy at the Christie NHS Foundation Trust (Manchester, UK); Independent dose calculation for protons and carbon ions at the MedAustron Ion Therapy center (Wiener Neustadt, Austria). Conclusions: GATE‐RTion builds the bridge between researchers and clinical users from the OpenGATE collaboration in the field of Light Ion Beam Therapy. The applications presented in three European facilities using three completely different machines (three different vendors, cyclotron‐ and synchrotron‐based systems, protons, and carbon ions) demonstrate the relevance and versatility of this project.